Oxygen‐Bridged Ga2(Et)3(OTeF5)3 and the Weakly Coordinating Anions [Ga(Et)(OTeF5)3]− and [Ga(OTeF5)4]−. Issue 44 (8th July 2019) - Wiesner, Anja; Fischer, Lukas; Steinhauer, Simon; Beckers, Helmut; Riedel, Sebastian
Abstract: Salts of the weakly coordinating anions [Ga(OTeF5 )4 ] − as well as [Ga(Et)(OTeF5 )3 ] − and the neutral Ga2 (Et)3 (OTeF5 )3 were synthesized and characterized by spectroscopic methods and single‐crystal X‐ray diffraction. Ga2 (Et)3 (OTeF5 )3 was formed by treating GaEt3 with pentafluoroorthotelluric acid (HOTeF5 ) and reacted with PPh4 Cl and CPh3 Cl to [PPh4 ][Ga(Et)(OTeF5 )3 ] and [CPh3 ][Ga(Et)(OTeF5 )3 ]. In contrast, Ag[Ga(OTeF5 )4 ] was prepared from AgOTeF5 and GaCl3 and was used as a versatile starting material for further reactions. Starting with Ag[Ga(OTeF5 )4 ] the substrates [PPh4 ][Ga(OTeF5 )4 ] and [CPh3 ][Ga(OTeF5 )4 ] were formed from PPh4 Cl and CPh3 Cl. Abstract : Weakly coordinating, yet powerful : The synthesis and characterization of the two weakly coordinating anions [Ga(Et)(OTeF5 )3 ] − and [Ga(OTeF5 )4 ] − is reported. Both compounds are prepared in an easy one‐pot procedure in quantitative yield. Their molecular structure and spectroscopic data are compared. Furthermore, the intermediate of the synthesis of [Ga(Et)(OTeF5 )3 ] − is described. Ga2 (Et)3 (OTeF5 )3 reacts the chloride sources but not with additional HOTeF5 . This allowed us to have a closer look at the bond situation of gallium.